Occurrence and Impact of Gastrointestinal Bleeding and Major Adverse Cardiovascular Events during Sepsis: A 15-Year Observational Study - Ming-Shun Hsieh; Shu-Hui Liao; Vivian Chia-Rong Hsieh; Chorng-Kuang How (Emergency Medicine International)
Objective. Sepsis patients are at risk of gastrointestinal bleeding (GIB) and major adverse cardiovascular events (MACEs), but few data are available on the occurrence of GIB and MACEs and their impact on sepsis outcomes. Methods. The medical claims records of 220,082 patients admitted for sepsis between 1999 and 2013 were retrieved from the nationwide database. The adjusted odds ratios (aORs) of composite outcomes including the hospital mortality, intensive care unit (ICU) admission, and mechanical ventilation (MV) in patients with a MACE or GIB were estimated by multivariate logistic regression and joint effect analyses. Results. The enrollees were 70.15 ± 15.17 years of age with a hospital mortality rate of 38.91%. GIB developed in 3.80% of the patients; MACEs included ischemic stroke in 1.54%, intracranial hemorrhage (ICH) in 0.92%, and acute myocardial infarction (AMI) in 1.59%. Both ICH and AMI significantly increased the risk of (1) ICU admission (aOR = 8.02, 95% confidence interval (CI): 6.84–9.42 for ICH and aOR = 4.78, 95% CI: 4.21–5.42 for AMI, respectively), (2) receiving MV (aOR = 3.92, 95% CI: 3.52–4.40 and aOR = 1.99, 95% CI: 1.84–2.16, respectively), and (3) the hospital mortality (aOR = 1.08, 95% CI: 0.98–1.19 and aOR = 1.11, 95% CI: 1.03–1.19, respectively). However, sepsis with GIB or ischemic stroke increased only the risk of ICU admission and MV but not the hospital mortality (aOR = 0.98, 95% CI: 0.93–1.03 for GIB and aOR = 0.84, 95% CI: 0.78–0.91 for ischemic stroke, respectively). Conclusions. GIB and MACEs significantly increased the risk of ICU admission and receiving MV but not the hospital mortality, which was independently associated with both AMI and ICH. Early prevention can at least reduce the complexity of clinical course and even the hospital mortality.